"The outside is always an inside": the idea of space and its theoretical heritage in "Toward an architecture". Issue 3 (2nd July 2016) - Cattaneo, Daniela Alejandra; Cutruneo, Jimena Paula
Abstract: The article proposes to delve deeper in the idea of space in Le Corbusier's Toward an Architecture (1923), focalizing in its connections with the past and urban design. When in his book Le Corbusier presents his " trois rappels a messieurs les architectes" – volume, surface and plan (in its broad sense) – he outlines the keys to his idea of space. It proves imperative to use Le Corbusier's original term " Rappel " as its word play transcends any possible translation. Space is therefore defined as a Rappel (call) to architects, but also as a Rappel (reminder, evocation) to multiple theorizations and ideas that have traversed architecture throughout history. Le Corbusier's argument understands the directions of space as an extension, showing his affiliation with a tradition of French thinking that, in architecture, subscribes since Viollet le Duc to the Cartesian Method, in which spatiality is understood – from the Barroque – both Outside and Inside. It is proven that, in clear continuity with French architectural tradition and drawing inspiration from the ideas of Auguste Choisy, Le Corbusier defines with the mass and the void a space in which "the Outside is always an Inside". Thus, it is demonstrated that not only the links with the past but also the material resources for the definition of such space are common in different scales, from the definition of an inside up to the urban design.